N Nilai-Nilai Pembangun Karakter Dalam Ajaran Hindu - Putu Trisna Sintyadewi (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The purpose of this paper is to analyze in depth the teachings of character which are behaviors that are visible or possessed by each human which can be seen in actions and attitudes towards all people based on religious teachings or truth. This apparent behavior will be seen clearly and can be influenced by various things, such as positive or negative things, depending on how the environment provides teaching and understanding of character teachings through values ​​that must be known by all humans. Because the character is a reflection of the values ​​that are formed in each of us which are obtained through education, experience, and environmental influences. character certainly has values ​​that aim to provide understanding as well as guides in living life anywhere and anytime. The importance of writing in order to be able to analyze the values ​​of character building in Hinduism because through these values ​​will be the bridge that connects everyone to create a good, useful and beneficial person for himself and others. Keywords: Character Values, Hindu Teachings